Multilayer Pt/Al based ohmic contacts for AlGaN/GaN heterostructures stable up to 600°C ambient air. (February 2016) - Goyal, Nitin; Dusari, Srujana; Bardong, Jochen; Medjdoub, Farid; Kenda, Andreas; Binder, Alfred
Highlights: Pt/Al multilayer stack-based ohmic contact metallization for AlGaN/GaN heterostructures. Excellent stability of the proposed metallization for extreme environment applications. More than 100 h of continuous aging tests at 600°C in air. I – V characteristics of the fabricated samples show excellent linearity after the aging. Potential for GaN based extreme environment sensing/device solutions. Abstract: In this paper, we present a Pt/Al multilayer stack-based ohmic contact metallization for AlGaN/GaN heterostructures. Circular transmission line method (CTLM) structures were fabricated to assess the electrical properties of the proposed metallization. The fabricated stack shows excellent stability after more than 100 hours of continuous aging at 600°C in air. Measured I – V characteristics of the fabricated samples show excellent linearity after the aging. The Pt/Al-based metallization shows great potential for future device and sensor applications in extreme environment conditions.